SPECT Findings in Alzheimer’s Disease and Parkinson’s Disease with Dementia - S. E. Starkstein; S. Vázquez; G. Petracca; L. Sabe; M. Merello; R. Leiguarda (Behavioural Neurology)
We examined, with single photon emission tomography (SPECT) and (99mTc)-HMPAO, 18 patients with idiopathic Parkinson's disease and no dementia (PD), 12 patients with PD and dementia, 24 patients with probable Alzheimer's disease (AD), and 14 controls. While the three patient groups showed significantly lower perfusion in frontal inferior and temporal inferior areas as compared to controls, both demented groups showed significantly more severe bilateral hypoperfusion in superior frontal, superior temporal and parietal areas as compared to non-demented PD patients and controls. On the other hand, no significant differences in cerebral perfusion were found between patients with AD and patients with PD and dementia. In conclusion, our findings demonstrated specific but similar cerebral perfusion deficits in demented patients with either AD or PD.